ASSESSMENT OF OCCUPATIONAL RADIATION DOSE FROM CAMERA MODEL INTRAORAL HANDHELD X-RAY DEVICE WITHOUT STRAY RADIATION PROTECTION SHIELD. Issue 1 (6th January 2022) - Moshfeghi, Mahkameh; Safi, Yaser; Afzalan, Alireza; Ghazizadeh Ahsaie, Mitra
Abstract: The aim of this study was to assess the occupational exposure from portable X-ray device without stray radiation protection shield measured using thermoluminescent dosemeters (TLDs). A total of 108 intraoral periapical radiographies of six sextants were performed. The TLDs were located on right index finger and left palm, between the pupils of the eyes at the edges of the Nasion point, Manubrium of Sternum bone and genital area. The detected mean doses per procedure were 70, 99, 60, 51, 51 and 58 μSv in the right finger, left palm, level of the Nasion point, under left clavicle, above the sternum manubrium and at the gonad area, respectively. Maximum number of radiographic images that the operator is allowed to perform depends on eye exposure and in accordance with International Commission on Radiological Protection is 0.16 (0.12–0.23) per hour or 1.28 (0.96–1.84) per day.